(3eNJUQ bhJ GdbdhHs - (3CHh WGdH Gdecj , eMeO Hf Ydj Hf YWjI GdMGQKj, CHh WGdH Gdecj,J (B386 (3g` s ((3jhfS GdTQfLi GdgeQeRi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi dGjfSi ef PcQg hHYO agPg fHPg dWjaI ef eNJUQ bhJ GdbdhH dSjOfG CHh WGdH Gdeci HGH eQGYGg Gdfjg ai GdC(B'(3eGd dCfgG CSGS dLejY GdYeGd s
(3BNQgG (B:s
(3hbO SFd QShd Gddg Udi Gddg Ydjg hSde Yf bhdg YR hLd (B:" (3GdPjf BefhG hde jdHShG CjeGfge HXde dCjI (B" (3ef gDdGA abGd ef HQj jejfg hUOb dSGfg hGSJbGe bdH hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3hQO ai cTa GdXfhf ai L(B2 (3U` (B1361 (3Cf bhJ GdbdhH ai eYGedI GdeMHHhH dCHh WGdH eMeO Hf Ydi Hf YWjI Gdeci s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdeLGejYs